Analysis of Learning Management System Needs in Madrasah Ibtidaiyah Teacher Education Study Program - Salmilah; Ahmad Munawir (South Sulawesi Education Development (SSED), 2024)
The study aimed to evaluate the use of the Learning Management System (LMS) in the Madrasah Ibtidaiyah Teacher Education Study Program. The type of research used is quantitative data collection techniques using questionnaires and interviews. The study's respondents were lecturers and students of the Madrasah Ibtidaiyah Teacher Education Study Program. This research was conducted in the academic year 2023/2024. The results showed that the SIBEDDU LMS was no longer used. The college's LMS uses the Virtual Classroom developed by IAIN Palopo as a replacement. 80% of lecturers are aware of the existence of LMS, but 100% do not use it. Lecturers prefer external LMSs such as Zoom and Google Classroom. Students use the LMS to access materials, submit assignments, participate in discussion forums, and take online exams. The suggestions were the need for improvements to the VCLASS LMS, such as simplifying navigation and paying attention to access speed constraints as well as adequate servers and the preparation of special training for lecturers and students so that they can make good use of the LMS. In addition, developing new features that suit the needs of lecturers and students, such as focusing on developing interactive features such as live discussion forums and integration with digital libraries, as well as further research, can explore the development of LMS-specific features that increase interactivity and user engagement.